1989
DOI: 10.1083/jcb.108.3.885
|View full text |Cite
|
Sign up to set email alerts
|

Activators of protein kinase C trigger cortical granule exocytosis, cortical contraction, and cleavage furrow formation in Xenopus laevis oocytes and eggs.

Abstract: Abstract. Prophase I oocytes, free of follicle cells, and metaphase II eggs of the amphibian Xenopus laevis were subjected to transient treatments with the protein kinase C activators, phorbol 12-myristate 13-acetate (PMA), phorbol 12,13-didecanoate, and 1-olyeoyl-2-acetyl-sn-glycerol. In both oocytes and eggs, these treatments triggered early events of amphibian development: cortical granule exocytosis, cortical contraction, and cleavage furrow formation. Surprisingly, activation of oocytes occurred in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 58 publications
4
58
0
Order By: Relevance
“…Phosphorylation studies suggest that PKC inhibits cleavage furrow formation (Satterwhite et al, 1992) and a phorbol ester has been found to inhibit cleavage in mouse oocytes (Niemierko and Komar, 1985). Because phorbol esters rapidly down-regulate at least one PKC isozyme in Xenopus (Sahara et al, 1992), phorbol ester may induce cleavage furrow formation in Xenopus [for review, Bement and Capco (1989, 1990, 1991a Significance of the DAG Changes The timing of the PKC activation is crucial because events such as cortical granule breakdown and cleavage may be due to PKC (see review by Bement, 1992). In Xenopus, the initial increases in DAG and PKC activation are after the peaks of [Ca2+]i (Busa et al, 1985b) or IP3 (Stith et al, 1993(Stith et al, , 1994.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation studies suggest that PKC inhibits cleavage furrow formation (Satterwhite et al, 1992) and a phorbol ester has been found to inhibit cleavage in mouse oocytes (Niemierko and Komar, 1985). Because phorbol esters rapidly down-regulate at least one PKC isozyme in Xenopus (Sahara et al, 1992), phorbol ester may induce cleavage furrow formation in Xenopus [for review, Bement and Capco (1989, 1990, 1991a Significance of the DAG Changes The timing of the PKC activation is crucial because events such as cortical granule breakdown and cleavage may be due to PKC (see review by Bement, 1992). In Xenopus, the initial increases in DAG and PKC activation are after the peaks of [Ca2+]i (Busa et al, 1985b) or IP3 (Stith et al, 1993(Stith et al, , 1994.…”
Section: Discussionmentioning
confidence: 99%
“…DAG, the other second messenger, may also play a role in fertilization. By acting as an activator of protein kinase C (PKC; Nishizuka, 1992), DAG may induce DAG, sn-1,2-diacylglycerol; IP3, inositol 1,4,5-trisphosphate; MBS, modified Barth's solution; PA, phosphatidic acid; PC, phosphatidylcholine; PIP2, phosphatidylinositol 4,5-bisphosphate; PKC, protein kinase C. resumption of endocytosis (Vasilets et al, 1990;Khan et al, 1991), cortical contraction, cortical granule exocytosis, chromosome decondensation, nuclear envelope and Golgi reformation, and cleavage furrow formation in Xenopus laevis (Bement and Capco, 1989, 1990, 1991a. PKC may be responsible for elevation of intracellular pH in sea urchin fertilization (Shen and Buck, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the possible involvement of PKC in the oocyte activation process (Colonna et al, 1997;Green et al, 1999;Sedmíková et al, 2006) and the exocytosis of CGs (Bement and Capco, 1989;Fan et al, 2002). PKC belongs to the serine/threonine kinase, and 12 isoforms are known, being classified into three groups.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional, resin-embedded transmission electron microscopy has been utilized by investigators as a powerful tool to interrogate the ultrastructural changes that accompany www.intechopen.com fertilization (Bement and Capco, 1989;Gallicano et al, 1991Gallicano et al, , 1994. However, mammalian eggs and embryos do not afford high contrast images in resin-embedded, ultrathin sections (silver to gold interference patterns corresponding to 60-70 nm).…”
Section: Conventional and Embedment-free Electron Microscopymentioning
confidence: 99%